2012
DOI: 10.1128/jvi.06712-11
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Intra- and Interhost Dynamics to Norovirus Evolution

Abstract: c Norovirus (NoV) is an emerging RNA virus that has been associated with global epidemics of gastroenteritis. Each global epidemic arises with the emergence of novel antigenic variants. While the majority of NoV infections are mild and self-limiting, in the young, elderly, and immunocompromised, severe and prolonged illness can result. As yet, there is no vaccine or therapeutic treatment to prevent or control infection. In order to design effective control strategies, it is important to understand the mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
118
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 111 publications
(126 citation statements)
references
References 72 publications
(101 reference statements)
7
118
0
1
Order By: Relevance
“…From these limited studies, it is difficult to discern whether there are characteristics of chronic norovirus infection that are broadly applicable to all populations and characteristics that are true to specific populations, or whether characteristics vary by each individual case. Previous work has shown that during the course of chronic infection, virus genetic diversity can expand quickly (22,23,25,35); however, it was previously unknown whether this genetic variation translated into antigenic variation or the emergence of antigenically unique isolates that differ significantly from contemporary epidemic strains. For the first time, our work clearly demonstrates the potential for significant antigenic variation over the course of chronic infection within an individual, which is important in terms of therapeutic treatment considerations and for studying the potential role of chronic shedders as reservoirs for evolving new outbreak strains.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…From these limited studies, it is difficult to discern whether there are characteristics of chronic norovirus infection that are broadly applicable to all populations and characteristics that are true to specific populations, or whether characteristics vary by each individual case. Previous work has shown that during the course of chronic infection, virus genetic diversity can expand quickly (22,23,25,35); however, it was previously unknown whether this genetic variation translated into antigenic variation or the emergence of antigenically unique isolates that differ significantly from contemporary epidemic strains. For the first time, our work clearly demonstrates the potential for significant antigenic variation over the course of chronic infection within an individual, which is important in terms of therapeutic treatment considerations and for studying the potential role of chronic shedders as reservoirs for evolving new outbreak strains.…”
Section: Discussionmentioning
confidence: 99%
“…However, some immu-nocompromised individuals, such as transplant patients on immunosuppressive drugs, those with primary immunodeficiencies, cancer patients undergoing chemotherapy, and those with HIV infections, may develop chronic norovirus infection. Symptomatic infection and virus shedding in these patients can persist for weeks to years (20)(21)(22)(23)(24)(25) and can result in medical issues, such as dehydration and nutrient deficiencies (26), making development of treatment options for these patients an important priority. Unfortunately, there are no approved therapeutics or vaccines for controlling norovirus infections.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Des travaux sur les cardiovirus humains ont ainsi mis en évidence la trace d'une recombinaison avec un theilovirus de rat, suggérant que l'ancêtre commun de ces virus proviendrait du rat [35]. La puissance de ces méthodes permet par ailleurs de caractériser la dynamique évolutive des virus chez un hôte ou entre différents hôtes [36]. La génération de la diversité peut également être explorée dans différents sites chez un même hôte et ce en fonction du développement de l'infection [37].…”
Section: Métagénomique Virale Et Connaissance éPidémiologiqueunclassified